Implementasi Good Governance Pada Pemerintahan Nagari Aie Angek Kecamatan X Koto Kabupaten Tanah Datar dalam Program Keluarga Harapan PKH - Rayhanil Kamila; Heru Permana Putra (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2025)
Good Governance is a concept of how to manage a good government organization, about how a nation distributes power and manages resources and various problems faced by society. Governance involves many interested actors or stakeholders, which basically consist of the government, the private sector and civil society. The problem raised in this article is how to implement the principles of transparency and accountability in determining recipients of PKH social assistance in Nagari Aie Angek in realizing good governance. The research method used is a qualitative method with a descriptive approach. The data used in this research are primary data and secondary data. Data management is carried out by analyzing data obtained through interviews and documentation, then testing the validity of the data to prove that the data obtained corresponds to the facts that occurred. The results of this research show that the implementation of the principles of transparency and accountability in determining recipients of PKH social assistance in Nagari Aie Angek has been carried out well in accordance with applicable regulations. The lack of transparency and accountability from the government is due to the fact that most KPMs have behavior that does not reflect that they are recipients of social assistance, such as their lifestyle which appears to be like that of well-off people, things like this have led to the opinion that the distribution of PKH social assistance is always misdirected every year. Regarding the government's performance in realizing good governance in Nagari Aie Angek, this can be seen from the implementation of good governance principles that have been carried out or implemented in daily activities. However, it cannot be denied that being something good will not be free from more or less mistakes.